2000
DOI: 10.1086/303082
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal and Fetal Methylenetetrahydrofolate Reductase Genetic Polymorphisms: An Examination of C677T and A1298C Mutations

Abstract: Methylenetetrahydrofolate reductase (MTHFR) mutations are commonly associated with hyperhomocysteinemia, and, through their defects in homocysteine metabolism, they have been implicated as risk factors for neural tube defects and unexplained, recurrent embryo losses in early pregnancy. Folate sufficiency is thought to play an integral role in the phenotypic expression of MTHFR mutations. Samples of neonatal cord blood (n=119) and fetal tissue (n=161) were analyzed for MTHFR C677T and A1298C mutations to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
124
5
10

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 202 publications
(148 citation statements)
references
References 18 publications
(22 reference statements)
9
124
5
10
Order By: Relevance
“…12 A recent study by Volcik et al 11 has even demonstrated the existence of a MTHFR 677TT/1298CC genotype in a living Hispanic woman who had a child with spina bifida, providing further evidence that recombinant events between MTHFR mutation loci do occur despite their short physical distance of 2.1 kb. 8 In an adult Canadian population of predominantly European (Celtic) descent and other ethnic backgrounds, we have demonstrated a relatively high frequency of 677TT/1298AC genotypes, ranging from 9.2 to 12.5% in study and control groups, respectively, indicating a strong incidence of cis MTHFR mutations in this population. 9,13 This is in contrast to Weisberg et al 5 who studied Canadian groups of 133 children with spina bifida and 141 mothers of children with spina bifida and discovered only a single child with a MTHFR 677TT/1298AC genotype.…”
mentioning
confidence: 67%
See 3 more Smart Citations
“…12 A recent study by Volcik et al 11 has even demonstrated the existence of a MTHFR 677TT/1298CC genotype in a living Hispanic woman who had a child with spina bifida, providing further evidence that recombinant events between MTHFR mutation loci do occur despite their short physical distance of 2.1 kb. 8 In an adult Canadian population of predominantly European (Celtic) descent and other ethnic backgrounds, we have demonstrated a relatively high frequency of 677TT/1298AC genotypes, ranging from 9.2 to 12.5% in study and control groups, respectively, indicating a strong incidence of cis MTHFR mutations in this population. 9,13 This is in contrast to Weisberg et al 5 who studied Canadian groups of 133 children with spina bifida and 141 mothers of children with spina bifida and discovered only a single child with a MTHFR 677TT/1298AC genotype.…”
mentioning
confidence: 67%
“…8 The absence of 677CT/1298CC and 677TT/1298CC genotype combinations in our neonatal control group 8 provides strong evidence that compound triple and quadruple MTHFR mutations may be associated with compromised foetal viability. There has been some criticism with the MboII restriction fragment length polymorphism detection of A1298C mutations, due to possible interference from silent T1317C mutations 5 however, these criticisms are unfounded, especially since the identification of mutated alleles would not be compromised.…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…These data, together with the studies mentioned above, demonstrate that 677T and 1298C alleles in cis are possible, but indeed very rare, and support the hypothesis that triple mutation combinations probably reflect recombinant events having occurred either de novo or in the relatively late ancestral history of specific sub-populations. Obviously, it is not excluded that specific subpopulations, such as the ones studied by Isotalo et al 10,11 may display higher frequencies of triple (and possibly quadruple) mutation combinations. In these sub-populations it is also possible that triple and quadruple mutation combinations may have a negative influence on embryonic survival.…”
mentioning
confidence: 97%